PENGEMBANGAN GAME EDUKASI UNTUK MENINGKAT HASIL BELAJAR PADA MATA PELAJARAN BAHASA INGGRIS KELAS XI DI SMAN 4 SIDRAP - Furkan Harris Saputra; Abdul Hakim; Farida Febriati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to: (1) Knowing the level of need for educational games on English subjects of class XI at SMAN 4 SIDRAP (2) Designing educational games on English subjects of class XI at SMAN 4 SIDRAP (3) Knowing the level of validity, practicality of using educational games on English subjects of class XI at SMAN 4 SIDRAP, The research followed the stages of development of Alessi and Trollip, which consisted of development steps (Planning, Design, & Development). This research was conducted at SMAN 4 SIDRAP involving students of grade XI and English subject educators of grade XI. The test of the developed product consists of an alpha test which is validated by 3 validators including instrument validators, content/material validators with an average score of 100% which is in very good qualifications, media validators with an average score of 96% which is in very good qualifications. The beta test consists of a large group trial involving 30 students whose final questionnaire results are 89.7%, which is in the Practical qualification, Small group trials involving 12 students whose final questionnaire results were 97.7% were in very practical qualifications. Educators' responses related to the development of educational games with the final results of the questionnaire 98% are in very practical qualifications. This development research produces educational game products that can be used in the learning process for class XI students at SMAN 4 SIDRAP. The learning outcomes of students after using educational games increased by 0.21 or 21.46%.